The burden of stillbirths in low resource settings in Latin America: Evidence from a network using an electronic surveillance system. - Bremen de Mucio; Claudio Sosa; Mercedes Colomar; Luis Mainero; Carmen M Cruz; Luz M Chévez; Rita Lopez; Gema Carrillo; Ulises Rizo; Erika E Saint Hillaire; William E Arriaga; Rosa M Guadalupe Flores; et al. (PLoS ONE)
Objective To determine stillbirth ratio and its association with maternal, perinatal, and delivery characteristics, as well as geographic differences in Latin American countries (LAC). Methods We analysed data from the Perinatal Information System of the Latin American Center for Perinatology and Human Development (CLAP) between January 2018 and June 2021 in 8 health facilities from five LAC countries (Bolivia, Guatemala, Honduras, Nicaragua, and the Dominican Republic). Maternal, pregnancy, and delivery characteristics, in addition to pregnancy outcomes were reported. Estimates of association were tested using chi-square tests, and P < 0.05 was regarded as significant. Bivariate analysis was conducted to estimate stillbirth risk. Prevalence ratios (PR) with their 95% confidence intervals (CI) for each predictor were reported. Results In total, 101,852 childbirths comprised the SIP database. For this analysis, we included 99,712 childbirths. There were 762 stillbirths during the study period; the Stillbirth ratio of 7.7/1,000 live births (ranged from 3.8 to 18.2/1,000 live births across the different maternities); 586 (76.9%) were antepartum stillbirths, 150 (19.7%) were intrapartum stillbirths and 26 (3.4%) with an ignored time of death. Stillbirth was significantly associated with women with diabetes (PRadj 2.36; 95%CI [1.25-4.46]), preeclampsia (PRadj 2.01; 95%CI [1.26-3.19]), maternal age (PRadj 1.04; 95%CI [1.02-1.05]), any medical condition (PRadj 1.48; 95%CI [1.24-1.76, and severe maternal outcome (PRadj 3.27; 95%CI [3.27-11.66]). Conclusions Pregnancy complications and maternal morbidity were significantly associated with stillbirths. The stillbirth ratios varied across the maternity hospitals, which highlights the importance for individual surveillance. Specialized antenatal and intrapartum care remains a priority, particularly for women who are at a higher risk of stillbirth.